2019
DOI: 10.1155/2019/3276958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 600 mg Alpha-lipoic Acid Supplementation on Oxidative Stress, Inflammation, and RAGE in Older Adults with Type 2 Diabetes Mellitus

Abstract: Alpha-lipoic acid (ALA) has been used as a dietary supplement at different doses in patients with diabetes mellitus type 2 (T2DM) due to its antioxidant, anti-inflammatory, and hypoglycemic effects. However, the reports on the effects of ALA are controversial. For this reason, the purpose of the present study was to determine the effect of 600 mg/day of ALA on the markers of oxidative stress (OxS) and inflammation and RAGE in older adults with T2DM. A quasiexperimental study was carried out with a sample of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 46 publications
3
54
0
1
Order By: Relevance
“…Due to its ability to reduce OS and serum uric acid level, to improve general antioxidant capacity by increasing GSH level and GPx activity or to down-regulate NF-kB [42,63] and upregulate heme-oxygenase-1 expressions [41], the AL discontinuous treatment ameliorates the elevation of serum CRP, thus preventing the systemic inflammatory process induced by chronic fructose consumption. Even if there are studies that support a decrease in inflammatory markers under a treatment with AL in humans, the available data in this context of inflammation are quite controversial, probably due to the different characteristics of population and the variety of studies design [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to reduce OS and serum uric acid level, to improve general antioxidant capacity by increasing GSH level and GPx activity or to down-regulate NF-kB [42,63] and upregulate heme-oxygenase-1 expressions [41], the AL discontinuous treatment ameliorates the elevation of serum CRP, thus preventing the systemic inflammatory process induced by chronic fructose consumption. Even if there are studies that support a decrease in inflammatory markers under a treatment with AL in humans, the available data in this context of inflammation are quite controversial, probably due to the different characteristics of population and the variety of studies design [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, study by Masharani et al and Konrad et al because of low sample size were not included in this study. As a result, totally, 24 studies were included in the current systematic review and meta‐analysis, whereas 21, 18 and 11 studies were included in the meta‐analysis of the effects of ALA on BMI, weight and WC, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies employed a parallel design. Eighteen studies included both genders, and six studies included only female or male subjects. Most studies were conducted in China and Iran .…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al reported a significant reduction in serum levels of TC, LDL, and TG and a significant increase in HDL levels after intravenous administration of 600 mg ALA once daily for two weeks in obese-IGT patients [37]. In a study by Mendoza et al, after treatment with 600 mg ALA for six months in type 2 diabetic patients, a significant reduction in TC and an increase in HDL levels were reported; however, any significant change in TG levels was not observed [73]. In another study, supplementation with 600 mg ALA for 20 weeks in diabetic patients led to a nonsignificant effect on serum levels of TC, LDL, HDL, and TG [72].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 95%
“…* according to paired t-test; * * time to group interaction according to two-way repeated measure ANOVA. 8 Oxidative Medicine and Cellular Longevity glucose after supplementation with 600 mg ALA for six months [73]. In contrast, in one clinical study, after eight weeks of supplementation with 300 mg ALA in type 2 diabetic patients, an improvement in serum levels of glucose and HOMA-IR was reported [74].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%